Pelatihan Digitalisasi Usaha Kecil Menengah Melalui Program Peningkatan Kapasitas Koperasi Dan UKM - Erwin, Muhammad (Journal of Community Sustainability, 2025)
This community service activity aims to enhance the capacity of Small and Medium Enterprises (SMEs) in utilizing digital technology through business digitalization training integrated with the Cooperative and SME Capacity Building Program. The main problems faced by SMEs include low digital literacy and limited skills in marketing, financial record-keeping, and technology-based business management. The implementation method employed an educational and practical approach, consisting of needs analysis, interactive training, hands-on practice, mentoring, as well as monitoring and evaluation. The training materials covered the use of social media and marketplaces, digital financial recording, and product promotion and branding strategies. The results indicate an improvement in participants’ understanding and skills in using digital technology to support their business activities. Participants became more confident and motivated to gradually implement business digitalization. In addition, this activity strengthened the role of cooperatives as a platform for mentoring and empowering SMEs. Overall, the business digitalization training contributes positively to improving the competitiveness and economic independence of SMEs.